2012
DOI: 10.3329/bjpt.v19i1.10945
|View full text |Cite
|
Sign up to set email alerts
|

New records of Euglenophyceae for Bangladesh

Abstract: Eight newly recorded species of Euglenophyceae from Bangladesh have been illustrated and described in the present paper. The species are Euglena fundoversata L.P. Johnson, E. korshikovii Gojdics, E. minuta Prescott, E. sacculiformis Schiller, Lepocinclis truncata Da Cunha, Phacus pusillus Lemn., P. strongylus Pochm. and P. wettsteini Drez. IntroductionA series of papers on the members of Euglenophyceae have been published where 256 taxa have been described and illustrated (Islam and Aziz, 1979;Islam and Khondk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the members of Euglenophyceae have been made from different fresh water of habitats of Sylhet Division of Bangladesh. So far, there are large number of taxonomic studied of different species of Euglenophycean members were reported (Alfasane and Khondker, 2007;Alfasane et al 2010;Gani et al 2012. Khondker andAlfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In Dhaka city, Pagla Sewage Treatment Plant (PSTP) is one such lagoon which was investigated limnologically by Gani et al (2011). From the planktonic flora of this lagoon, nine new reports of Euglenophyceae for Bangladesh have been made (Gani et al 2012). A total of 34 phytoplankton samples were collected covering a period of one year from this lagoon (Gani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From the planktonic flora of this lagoon, nine new reports of Euglenophyceae for Bangladesh have been made (Gani et al 2012). A total of 34 phytoplankton samples were collected covering a period of one year from this lagoon (Gani et al 2012). A further detail investigation on these samples was carried out to see the quality of phytoplankton other than the members of Euglenophyceae.…”
Section: Introductionmentioning
confidence: 99%